2021
DOI: 10.1002/cad.20436
|View full text |Cite
|
Sign up to set email alerts
|

Physical teen dating violence in high school students in Slovenia: Prevalence and correlates

Abstract: Although teen dating violence (TDV) is internationally recognized as a serious threat to adolescents’ health and well‐being, almost no data is available for Slovenian youth. Hence, the purpose of this study was to examine the prevalence and predictors of TDV among Slovenian adolescents for the first time. Using data from the SPMAD study (Study of Parental Monitoring and Adolescent Delinquency), 330 high school students were asked about physical TDV victimization and perpetration as well as about their dating h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Moreover, the current evidence clearly shows that the occurrence of teen dating violence varies in relation to variables in adolescents' social environment. Exposure to violence in the family (Toplu-Demirtaş & Aracı-İyiaydın, 2021), having friends who engage in violent behavior (Baier et al, 2021), and experiencing low levels of informal control in the family and school context (Bertok et al, 2021) were all identified as correlates of teen dating violence, again confirming established findings from previous research.…”
Section: What Is the "Evidence" Required For Evidence-based Intervent...supporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, the current evidence clearly shows that the occurrence of teen dating violence varies in relation to variables in adolescents' social environment. Exposure to violence in the family (Toplu-Demirtaş & Aracı-İyiaydın, 2021), having friends who engage in violent behavior (Baier et al, 2021), and experiencing low levels of informal control in the family and school context (Bertok et al, 2021) were all identified as correlates of teen dating violence, again confirming established findings from previous research.…”
Section: What Is the "Evidence" Required For Evidence-based Intervent...supporting
confidence: 78%
“…Moreover, as Tomaszewska and Schuster (2021) highlight, the available evidence from Europe—just as from North America—predominantly examined dating violence among heterosexual youth, neglecting youth with a LGBTQIA+ identity. Moreover, as shown by the individual studies, the issue of gender differences in teen dating violence victimization and perpetration is still far from being resolved, with higher prevalence rates for physical dating violence perpetration among females found in some studies (Baier et al., 2021; Bertok et al., 2021), but not in others (Schuster et al., 2021; Toplu‐Demirtaş & Aracı‐İyiaydın, 2021). Moreover, comparing perpetration rates for male and female adolescents may yield different conclusions for different forms of dating violence (Oyarzún et al., 2021).…”
Section: What Is the “Evidence” Required For Evidence‐based Intervent...mentioning
confidence: 99%
See 1 more Smart Citation
“…The third contribution by Bertok et al. (2021) examines the prevalence rates and predictors of physical TDV among Slovenian adolescents using data from the SPMAD study (Study of Parental Monitoring and Adolescent Delinquency). This contribution addresses multiple settings of adolescents and includes individual‐level, peer‐, school‐ and family‐related variables as predictors of physical TDV victimization and perpetration.…”
Section: Contributionsmentioning
confidence: 99%
“…The results found in these studies corroborate patterns of gender differences found previously: Among heterosexual romantic partners, sexual violence is far more likely to be perpetrated by males, irrespective of the informant (Oyarzún et al., 2021; Tomaszewska & Schuster, 2021). In contrast, prevalence estimates based on self‐reported physical violence perpetration tend to show higher rates for female than for male adolescents (Baier et al., 2021; Bertok et al., 2021; Tomaszewska & Schuster, 2021; Toplu‐Demirtaş & Aracı‐İyiaydın, 2021). Self‐reported physical victimization rates were found to be broadly similar for bother genders.…”
Section: Introductionmentioning
confidence: 99%